Not just 'a few wisps': real-time measurement of tobacco smoke at entrances to office buildings. Issue 3 (21st December 2010) - Kaufman, Pamela; Zhang, Bo; Bondy, Susan J; Klepeis, Neil; Ferrence, Roberta
Abstract : Introduction: An unintended consequence of indoor smoking restrictions is the relocation of smoking to building entrances, where non-smokers may be exposed to secondhand smoke, and smoke from outdoor areas may drift through entrances, exposing people inside. Tobacco smoke has been linked to numerous health effects in non-smokers and there is no safe level of secondhand smoke (SHS) exposure. This paper presents data on levels of tobacco smoke inside and outside entrances to office buildings. Methods: Real-time air quality monitors were used to simultaneously measure respirable particulate matter (PM2.5 ; air pollutant particles with a diameter of 2.5 μm or less) as a marker for tobacco smoke, outside and inside 28 entrances to office buildings in downtown Toronto, Ontario, in May and June 2008. Measurements were taken when smoking was and was not present within 9 m of entrances. Background levels of PM2.5 were also measured for each session. A mixed model analysis was used to estimate levels of PM2.5, taking into account repeated measurement errors. Results: Peak levels (10 s averages) of PM2.5 were as high as 496 μg/m 3 when smoking was present. Mixed model analysis shows that the average outdoor PM2.5 with smoking was significantly higher than the background level (p<0.0001), and significantly and positively associated with the number of lit cigarettes (p<0.0001). The average level of PM2.5 with ≥5 lit cigarettes was 2.5 times greater than the average background level. Conclusions: These findings support smoke-free policies at entrances to buildings to protect non-smokers from exposure to tobacco smoke.